Towards new cesium containing manganese vanadates via a precursor method. Issue 39 (13th September 2021) - Zou, Yan-Min; Lan, Xiao-Yun; Ma, Wen; Jin, Jian-Ce; Sun, Hai-Yan; Li, Ji-Long; Feng, Mei-Ling; Huang, Xiao-Ying
Abstract : The first two 3D cesium containing manganese vanadates were synthesized by using K2 Mn(VO3 )4 as the precursory reactant in concentrated Cs + aqueous solutions. Abstract : Two new cesium containing manganese vanadates are synthesized by a facile method. The known compound K2 Mn(VO3 )4 (1 ), synthesized via a milder method than the previous hydrothermal reaction, was firstly used as a precursor to prepare two new manganese vanadates, namely CsMn(VO3 )3 ·H2 O (2 ) and Cs4.34 Mn1.83 (VO3 )8 ·2.965H2 O (3 ) in concentrated Cs + aqueous solutions at 80 °C. Compound 2 features a three-dimensional (3D) microporous framework constructed from serrated (VO3 ) n chains interconnected by Mn 2+ ions. The Cs + ions and the lattice water molecules are located in the channels of the structure along the a -axis. In compound 3, the sinusoidal (VO3 ) n chains are linked by Mn 2+ ions into V–O–Mn double chains, which are further weaved by Mn4 O8 units to form a 3D microporous network with channels occupied by disordered Cs + ions. Compounds 2 and 3 are the first Cs–Mn–V–O examples with a 3D microporous framework. Thermal stabilities of compounds 2 and 3 were investigated by thermogravimetric (TG) analysis. This work provides an effective synthetic method for preparing alkali-metal containing heterometallic vanadates with new composition and structures.